Effect of samarium on microstructure and corrosion resistance of aged as-cast AZ92 magnesium alloy - 吴道高 颜世宏 王志强 张志琦 苗睿瑛 张小伟 陈德宏 (Journal of rare earths, 2014)
The effects of samarium（Sm） on microstructure and corrosion resistance of AZ92 magnesium alloy were characterized and analyzed by scanning electronic microscopy, X-ray diffraction, mass loss test, electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy and potentio-dynamic polarization test. The results showed that the added Sm could promote continuous precipitation of β-Mg17Al12 phase in grains, and meanwhile restrain discontinuous precipitation of the same phase along the grain boundaries. Thus, the precipitations distributed more uniformly in the aged AZ92 magnesium alloys. When the content of Sm was 0.5 wt.%, the corrosion resistance of aged AZ92 alloy tended to be the best, which was due to the β-phase distributes more homogeneous reducing the galvanic corrosion. The corrosion product film had more integrality and compactness than AZ92 alloys without Sm. However, it resulted in worse corrosion resistance of AZ92 alloy because of the formation of mass cathodic Al2 Sm phase coming from excess Sm in AZ92 alloy.